PB 19 Taste-related responses from the human nucleus accumbens and the hypothalamus obtained by invasive electrophysiology. Issue 10 (October 2017) - Münte, T.; Heldmann, M.; Brüggemann, N.; Rasche, D.; Zaehle, T.; Krauss, J.; Voges, J.; Tronnier, V.
Abstract : The taste is a fundamental property of food-stuff indicating palatability and safety as well as hedonic value of a food. Animal research as well as human neuroimaging work has suggested multiple brain areas involved in the processing of taste. Here, we take advantage of the fact that deep brain stimulation in neuropsychiatric diseases has targeted brain areas that have been implicated in homeostatic (hypothalamus) and hedonic (Nucleus accumbens) control of ingestive behavior. We recorded local field potentials in patients receiving DBS of the hypothalamus (patient 1: Cluster headache, patient 2: pain) or the Nucleus accumbens (patient 3: anorexia, patient 4: obsessive compulsive disease, patient 5: depression) while the electrodes were externalized for initial testing of the stimulation parameters. Patients first indicated favorite and disliked foods. These foods were applied in the following way. The patient was asked to put the food in his/her mouth, to keep it in the mouth to taste it (during this phase LFPs were obtained), to spit it out and to rinse the mouth with water. Subsequently, the next trial was applied. LFPs were obtained in a bipolar fashion and subjected to Fast Fourier Transform (FFT).Distinct peaks in the spectrum were obtained that differentiated liked and disliked food in the hypothalamus and Ncl. accumbens, indicating that both brain structures are sensitive to the hedonic quality of the food. Further studies are needed to investigate the state (hungry, satiated) and trait (high vs. low external drive for eating) dependency of these taste-related responses.